The Influence of Training, Teaching Experience, Principal Leadership, the Understanding of Curriculum to Teacher’s Performance - Afifah Asra; Syamsul Amar; Azwar Ananda (Fakultas Ilmu Pendidikan UNP)
The research aimed to get to identify: first the influence of training, teaching experience, principal leadership to the understanding of Social Science curriculum, second the influence of training, teaching experience, principal leadership, and the understanding of Social Science curriculum to teacher’s performance. This is a causal descriptive research. There are 57 teachers as research sample. This research findings were: first, there was a significant influence of training, teaching experience, principal leadership to the understanding of Social Science curriculum at state senior high schools in Pariaman City. The better of teacher training, good teaching experience, and good principal leadership, will be the better of teacher’s understanding of the curriculum. Second, there are was a significant influence of training, teaching experience, principal leadership, and understanding of curriculum toward teacher’s performance. The better of training, teaching experience, principal leadership, and understanding of the curriculum will be the better the teacher’s performance.